Review of Pre-Analytical Errors in Oral Glucose Tolerance Testing in a Tertiary Care Hospital - Nanda, Rachita; Patel, Suprava; Sahoo, Sibashish; Mohapatra, Eli (Journal of Nepal Health Research Council, 2018)
Background: The pre-pre-analytical and pre-analytical phases form a major chunk of the errors in a laboratory. The process has taken into consideration a very common procedure which is the oral glucose tolerance test to identify the pre-pre-analytical errors. Quality indicators provide evidence of quality, support accountability and help in the decision making of laboratory personnel. The aim of this research is to evaluate pre-analytical performance of the oral glucose tolerance test procedure. Methods: An observational study that was conducted overa period of three months, in the phlebotomy and accessioning unit of our laboratory using questionnaire that examined the pre-pre-analytical errors through a scoring system. The pre-analytical phase was analyzed for each sample collected as per seven quality indicators. Results: About 25% of the population gave wrong answer with regard to the question that tested the knowledge of patient preparation. The appropriateness of test result QI-1 had the most error. Although QI-5 for sample collection had a low error rate, it is a very important indicator as any wrongly collected sample can alter the test result. Conclusions: Evaluating the pre-analytical and pre-pre-analytical phase is essential and must be conducted routinely on a yearly basis to identify errors and take corrective action and to facilitate their gradual introduction into routine practice.